Chiral effects in normal and superconducting carbon nanotube-based nanostructures - Parafilo, A.V.; Krive, I.V.; Bogachek, E.N.; Landman, U.; Shekhter, R.I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The novel phenomenon of chiral tunneling in metallic single-wall carbon nanotubes is considered. It is induced by the interplay of electrostatic and pseudomagnetic effects in electron scattering in chiral nanotubes and is characterized by the oscillatory dependence of the electron transmission probability on nanotube chiral angle and the strength of the scattering potential. The appearance of a special (Aharonov–Bohm-like) phase in chiral tunneling affects various phase-coherent phenomena in nanostructures. We considered chiral effects in: (i) the persistent current in a circular nanotube, (ii) the Josephson current in a nanotube-based SNS junction, and (iii) resonant electron tunneling through a chiral nanotube-based quantum dot.